Acute Acalculus Cholecystitis in Dengue Hemorrhagic Fever-A Case Report - Mia, Md Abdul Ali; Mostafi, Mamun; Perveen, Shaila; Chowdhury, Niamul Gani; Ahmed, Mir Azimuddin; Rahman, SM Mizanur (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Presently Dengue appears with its varied features of presentation and progression. We report a case of acalculus cholecystitis in DHF from department of medicine, Combined Military Hospital, Dhaka. The patient presented with fever and diarrhea later developing abdominal pain. Her platelet counts were low and Dengue antibody test (Ig M) was positive with altered liver enzymes. Ultrasound showed thick walled gall bladder with clear lumen without stone or sluge, a feature of acute acalculous cholecystitis. The patient was successfully managed conservatively. J Bangladesh Coll Phys Surg 2017; 35(3): 155-157